Transformational Leadership Influence, Compensation, and Organizational Climate on Employee Performance with Work Motivation as Mediator Variable (Case Study at PT. Indo Traktor Utama) - Casmun Casmun; Rhian Indradewa; Tantri Yanuar R Syah; Diana Fajarwati (Penerbit Kemala Indonesia, 2021)
This study aimed to analyse the effect of transformational leadership on work motivation. Here; the analyse effect of compensation on work motivation and organizational climate on work motivation and effect of work motivation on employee performance at PT. Indo Traktor Utama has been studied. The correspondent sample of this study reached 180 respondents who are considered to have represented the population under study. In this study, we use the convenience sampling method, which is a sampling method based on the comfort factor of the respondent's place with research at the survey location. The analytical model also descriptive analysis and Structural Equation Modelling analysis with the Lisrel Program was performed in this study. The result shows that: first transformational leadership has a positive and significant influence on work motivation. These results imply that better transformational leadership is carried out by superiors at PT. Indo Traktor Utama, make better work motivation of its employees. Second, compensation has a positive and significant effect on work motivation. This means that the better compensation provided the higher work motivation. Third, organizational climate has a positive and significant effect on work motivation, this means that the better the organizational climate, the better work motivation, and fourth work motivation has a positive and significant effect on employee performance. This means that the better work motivation, the higher the performance of employees at PT. Indo Traktor Utama.